PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PEREDARAN KOSMETIK ILEGAL SECARA ONLINE - Rizal Satria Heryansyach; Rosalinda Elsina Latumahina (Gapenas Publisher, 2022)
Cosmetics are always favored by women, even from generation to generation there has never been a dim. Always needed in every appearance, even now cosmetics have become a basic need for women. In reality, cosmetics are products that must have a permit, the legality of which is a dead product. However, in fact not all cosmetics have this. In the end, it causes many problems that arise and are even considered detrimental to consumers and end compensation, etc. Consumers can take refuge behind the Consumer Protection Act, because every consumer is given a legal certainty and is guaranteed a sense of justice, security, etc. in the eyes of the law. Everything is interrelated. Not only selling and buying, but the BPOM permit is also very important considering that cosmetic products are not allowed to be circulated. Must go through many stages to finally be given a permit for a product fit for circulation, and must also comply with the applicable provisions regarding the product. Even though they do not directly meet with consumers, the obligations of business actors must also be carried out if they have entered the realm of trading, especially online/electronically